2020
DOI: 10.1002/nop2.604
|View full text |Cite
|
Sign up to set email alerts
|

Nursing experiences of COVID‐19 outbreak in Iran: A qualitative study

Abstract: Aim The global outbreak of coronavirus in 2020 was considered as a serious risk for healthcare providers, especially nurses. This study aimed to investigate nurses’ perceptions and experiences of COVID‐19 outbreak in Iran. Design This thematic analysis study was conducted in March 2020. Method Semi‐structured interviews were conducted with 24 nurses in Qazvin, Arak, Shiraz and Kashan cities of Iran. Results It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
100
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 25 publications
10
100
0
5
Order By: Relevance
“…These protective behaviours are also well described in the literature [10]. Moreover, some nurses reported that they separated themselves from their family especially at the beginning of the pandemic due to the high transmission rate, uncertainties of the disease, and possibility of being an asymptomatic carrier.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…These protective behaviours are also well described in the literature [10]. Moreover, some nurses reported that they separated themselves from their family especially at the beginning of the pandemic due to the high transmission rate, uncertainties of the disease, and possibility of being an asymptomatic carrier.…”
Section: Discussionmentioning
confidence: 60%
“…The literature declared that the majority of nurses report a sense of pride in being at the frontline [10] [14] [18]. In this study, the interns were very committed to their responsibilities and they believed that they should carry on and per-form at their maximum level of performance.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The need for ongoing managerial attention, support, and a visible presence was also noted. In Iran, Sadati et al [17] (2021) interviewed 24 hospital nurses during the March 2020 outbreak. They found a lack of preparedness, concern of exposure risk to themselves and their families, anxiety, along with a feeling that they were making a sacrificial commitment.…”
Section: Discussionmentioning
confidence: 99%
“…The crisis management includes preventive measures such as quarantine, social distancing, training citizens for hygienic practices, and hand washing. The final step is treatment at the advanced levels of the disease (4).…”
Section: Introductionmentioning
confidence: 99%